ANALYSIS OF INFLUENCE OF TAXES ON RESULTS OF ACTIVITY OF THE ORGANIZATIONS - Nailya D. Zaripova (Статистика и экономика)
In article the mechanism of inﬂ uence of taxes on various aspects of activity of theorganization (prime cost, revenue, proﬁt, pricing, etc.) depending on types of taxreveals: direct and indirect, conditional and constant and conditional and variable, and also depending on economic structureof the organization. Positive and negativeinﬂuence of taxes is opened.